2019
DOI: 10.1186/s41072-019-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors causing peak energy consumption of reefers at container terminals

Abstract: Reefers are refrigerated containers commonly used for transporting perishable goods such as meat, fish, vegetables and fruit. Nowadays, reefers are responsible for 40% of the total energy consumption of container terminals, when connected to the electricity grid on shore. Every time when a large number of reefers is plugged-in after arrival, peaks in energy consumption occur. As container terminals purchase energy using a demand-based fee, exceeding the reserved capacity during peak times increases the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…As the most critical intermediate node, the reefer operational fault refers to situations caused by failures in the reefer container handling processes, individual staff errors, or inconsistencies in the enterprise's system. An essential part of protecting the cold chain is to ensure that reefer containers are plugged into a reliable power supply, and power outage periods must be kept to a minimum (van Duin et al, 2019). Power supply interruptions inevitably occur during the container loading and unloading periods to the truck, port area, and ship.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…As the most critical intermediate node, the reefer operational fault refers to situations caused by failures in the reefer container handling processes, individual staff errors, or inconsistencies in the enterprise's system. An essential part of protecting the cold chain is to ensure that reefer containers are plugged into a reliable power supply, and power outage periods must be kept to a minimum (van Duin et al, 2019). Power supply interruptions inevitably occur during the container loading and unloading periods to the truck, port area, and ship.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…They concluded that the stacking effect of containers provides a thermal benefit to the power consumption of refrigerated containers located on the middle tier and bottom tier [32]. This effect was also noted in [28,37,56,57]. However, this approach was not verified in regard to perishable goods transport in refrigerated semi-trailers.…”
Section: Literature Reviewmentioning
confidence: 93%
“…On top of the port infrastructure, there is a service layer that utilizes physical assets and communication channels for performing essential maritime operations (DNV GL, 2015). Smart ports are enormous implementations of software, hardware, and communications channels (Gary C. Kessler & Steven D. Shepard, 2020).…”
Section: Research Environment For the Risks Assessment Processmentioning
confidence: 99%